Optimization of the Enzymatic Acylation Reaction Conditions of Vitis davidii Malvidin - Aili CAI; Mingyong HUANG; Zheng WANG; Yabo GUO; Qian ZHAO; Jiehong DENG (Shipin gongye ke-ji, 2022)
In order to increase the structural stability of anthocyanins, taking Vitis davidii malvidin as sample and the lipase CAL-B as catalyst, the effects of reaction time, temperature, and substrate molar ratio on enzymatic acylation were investigated. Based on the single factor experiments and taking the acylation rate as the response value, a response surface optimization experiment was designed to obtain the optimal process parameters for the enzymatic acylation reaction of Vitis davidii malvidin. Results showed that, the optimized parameters were as follows: The reaction time was 43 h, reaction temperature was 54 °C, substrate molar ratio was 1:24. Under these conditions, the acylation rate of malvidin was 49.92%±0.12%, this paper would provide important ideas for the stabilization and industrial production of Vitis davidii malvidin.